Ecological-economic analysis and valuation of biodiversity - Paulo A. L. D. Nunes; Jeroen C. J. M van den Bergh; Peter Nijkamp (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper introduces and surveys ecological-economic analysis and valuation of biodiversity. Furthermore, the notion and application of economic, monetary valuation of biodiversity is critically evaluated. A classification of biodiversity values is offered, based on a system of logical relationships among biodiversity, ecosystems, species and human welfare. Suggestions are made about which economic valuation methods can address which type of biodiversity value. The resulting framework is the starting point for a survey and evaluation of empirical studies at each of the four levels of diversity. The resulting monetary value estimates seem to give unequivocal support to the belief that biodiversity has a significant, positive social value. The contingent valuation method is by far the most used method. An important reason is that the other valuation methods are unable to identify and measure passive or nonuse values of biodiversity. Nevertheless, most studies lack a uniform, integrated perspective on biodiversity. Therefore, available economic valuation estimates should generally be regarded as providing a partial perspective on, and at best lower bounds, to the unknown value of biodiversity changes.
Keywords: Q20; 330; Biodiversity; biotic richness; use economic value; nonuse economic value; monetary values; contingent valuation; ecosystem health; integrated modeling; Artenvielfalt; Umweltökonomik; Theorie